2018
DOI: 10.1364/oe.26.018143
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear adaptive three-dimensional imaging with interferenceless coded aperture correlation holography (I-COACH)

Abstract: Interferenceless coded aperture correlation holography (I-COACH) is an incoherent digital holography technique for imaging 3D objects without two-wave interference. In I-COACH, the object beam is modulated by a pseudorandom coded phase mask (CPM) and propagates to the camera where its intensity pattern is recorded. The image of the object is reconstructed by a cross-correlation of the object intensity pattern with a point intensity response of the system, whereas the light from both the object and the point, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 23 publications
1
92
0
Order By: Relevance
“…Moreover, Lucy-Richardson method is not suitable for real-time monitoring as it is an iterative process and consumes more computational time compared to the other methods especially if the number of required iterations is large. By comparing the results, it is clear that the non-linear correlation has the minimum background noise and narrowest correlation peak for all types of angular variations due to its adaptive nature [20]. The execution time of the above methods are almost equal except that a longer time was noticed for the Lucy-Richardson method owing to its iterative nature.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, Lucy-Richardson method is not suitable for real-time monitoring as it is an iterative process and consumes more computational time compared to the other methods especially if the number of required iterations is large. By comparing the results, it is clear that the non-linear correlation has the minimum background noise and narrowest correlation peak for all types of angular variations due to its adaptive nature [20]. The execution time of the above methods are almost equal except that a longer time was noticed for the Lucy-Richardson method owing to its iterative nature.…”
Section: Methodsmentioning
confidence: 95%
“…However, studies conducted later revealed that the matched filter is not the ideal candidate for a decorrelation, as it suffers from substantial background noise. In this study, the decorrelation has been studied using a variety of filters and techniques, namely a matched filter, a phase-only filter [21], a non-linear correlation [20], a Wiener filter [22] and the Lucy-Richardson iterative algorithm [22]. The results are compared based on the background noise, computation time and the width of the correlation peak.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNR of the reconstructed images can be improved by recording multiple intensity patterns using different scatterers and averaging over the entire reconstructions as in the case of COACH systems [52]. Alternatively, improvement of the SNR can be achieved using a nonlinear correlator in which both spectral amplitudes of I OBJ and of I PSH are raised to a power of two independent parameters, which are optimized for maximum SNR [70,71].…”
Section: Imaging Through Scatterersmentioning
confidence: 99%
“…The system without the two-beam interference was named interferenceless COACH or I-COACH [19]. In the subsequent studies, the number of camera shots were reduced to two [20] and finally to one [21] via the development of the non-linear filter.…”
Section: Introductionmentioning
confidence: 99%